ANALISIS SEMIOTIKA IKLAN GOJEK EDISI RAMADHAN 2021 DI TENGAH PANDEMI COVID-19 - Nisa Eka Nastiti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
Ramadan in 2021 is the second year that it is recommended not to go home and meet with family and friends during this Covid-19 pandemic. This is a problem for people who are used to going home because they can’t meet their family and friends. The Covid-19 pandemic has changed the habits of many brands that initially only met the needs of their consumers but are now competing to provide solutions to their consumer problems. One of them is Gojek as a top of mind application that always answers the needs of its consumers, now providing many solutions. In this Ramadhan 2021, Gojek issued an advertisement which mainly said